Stick-Slip Instability in a Compliant Bistable Double-Slider Mechanism - Niknam, Alborz; Farhang, Kambiz (Journal of Applied Nonlinear Dynamics, 2026)
A This paper investigates friction-induced instability in a Single Degree-of-Freedom, pseudo-rigid-body representation of a bistable compliant mechanism composed of two sliders connected with a massless rigid link. The friction force is a function of the state variables through Stribeck effect and variable contact force due to the structural nonlinearity of the mechanism. A Constant normal force ensures the mass-belt contact during oscillation. It is shown that the steady-state response of the vibrating mechanism depends on the belt velocity, applied normal load, and stiffness. The applied normal force and belt velocity, as bifurcation parameters, are used to define the number and location of equilibrium points and their corresponding stability.